Economic performance and risk of farming systems specialized in perennial crops: An analysis of Italian hazelnut production. (November 2019) - Zinnanti, Cinzia; Schimmenti, Emanuele; Borsellino, Valeria; Paolini, Giulio; Severini, Simone
Abstract: Assessing farm profitability and economic risk is important to support farmers' decisions. Several factors affect yields and product prices, in turn influencing farmers' income level and economic risk. However, the literature has often neglected to explicitly account for the role of product quality. This is particularly important for crops such as hazelnut because farmers' prices vary according to the quality of the harvested product. Furthermore, it seems fundamental to disentangle the role of parameters influencing farm results, noticeably yield, product price and quality. This is because farmers select their risk management tools to satisfy their needs, but these are often suitable for managing the risk of only one of these parameters. Deploying a large sample of individual farm data over ten years, the profitability and risk of hazelnut production in the four main production areas in Italy are assessed. The analysis is performed by using a set of risk indicators, which are based on the distribution of the gross margin for hazelnuts. The results of this analysis suggest that Campania and Lazio are generally the most profitable regions while Sicily is the least profitable. Risk is quite high in all regions with Campania facing the lowest risk level. The sensitivity analysis, performed by combining Monte Carlo simulations and stepwise regression techniques, permits to establish that the most important parameter generating risk is yield, followed by product quality and, to a lesser extent, market price. These results suggest that hazelnut farmers could reduce their risk by using production insurances; there is also potential to develop tools suited to managing risks related to product quality. Highlights: Profitability and risk are quite high in hazelnut production in Italy despite differences among regions. Most of the risk is coming from yield, followed by product quality and, to a lesser extent, market price. Hazelnut farmers could benefit from a more extensive use of risk management tools and strategies. There is scope for developing tools to manage risks related to product quality.